A New Approach to Overcoming Mental Health Stigma through Inclusive Persuasive Communication - Rizka Aulia Arafah; Destiwati, Rita (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study examines the role of inclusive persuasive communication in influencing mindsets, viewpoints, and attitudes to improve. The high prevalence of mental health disorders dominated by Generation Z is caused by an environment full of stigma and discrimination. This research uses qualitative methods by referring to Hovland's Persuasive Communication to influence, change, and regulate the attitudes and behaviours of people with stigma. Inclusive Persuasive Strategy, chosen to find out how to design effective messages that are able to evoke emotions, empathy, and motivation for positive change based on Aristotle's Rhetoric to package information according to aspects that facilitate persuasion. Communication Accommodation Theory was chosen to look at the situations and conditions of individuals with mental health disorders when making adjustments as part of their efforts to deal with unfavourable situations. The results showed that individuals with mental health disorders focus on consuming information that is clear and relevant to their needs as a means of validating their feelings, emotions and conditions. When there is relevance to the individual's needs at that time, changes in attitude and behaviours will certainly occur. In accordance with the strategy and form of an inclusive approach, patterns of behaviours and emotional changes that occur need to be channelled and validated, where channelling and validating these emotions is characterized by recognition of the diversity of experiences and feelings.